Numerical Assessment of URM Infilled RC Frames Retrofitted With Near-Surface Mounted Reinforcing Steel Bars - Soti, Rajendra; Barbosa, Andre R.; Stavridis, Andreas (Frontiers in Built Environment, 2020)
This paper presents a study on a retrofit technique for masonry infilled reinforced concrete (RC) frames. The proposed retrofit technique involves the addition of reinforcing steel bars into epoxy-filled pre-cut grooves on the surface of infill walls. The feasibility of the developed technique is initially investigated experimentally through pull-out tests conducted on near-surface mounted (NSM) reinforcing steel bars. The experimental results are used to augment an existing nonlinear finite element modeling approach used to simulate the response of RC frames with the retrofitted infill panels and to calibrate the numerical models developed. The nonlinear finite element models employ smeared-crack and zero-thickness cohesive-crack interface elements to model the RC members and masonry infills, while nonlinear truss elements are used to model the reinforcing steel bars. The modeling scheme is used to numerically simulate the performance of one- and two-bay infilled RC frames with a variety of reinforcing steel retrofit configurations under lateral loads. The results indicate that the retrofit solution can improve the deformation capacity of existing infilled frames, and its effectiveness depends on the orientation and the distribution of the NSM reinforcement steel bars that are added to the infill panels.